Phytotoxicity of Graphene in Tomatoes and Bean - Cakir, Yuksel; Cakir, Ozgen U. Colak (IEEE, 2016)
The potential effects of graphene nano platelet (GNP) on the germination and seedling growth of terrestrial plants such as beans and tomatoes are investigated. The seeds of beans and tomatoes are soaked in a solution with varying concentrations (0, 500, 1000 and 2000 mg/L) of GNP. Seeds were exposed to the solution with and without nanoparticles and incubated at 25 degrees C until germination. Until germination, changes on the seeds are monitored. After 15 days of exposure to concentration, the number of the germinated seeds was counted and the lengths of the roots and shoots are measured and were dried in an oven at 60 degrees C for 24 hours. Their length and dry weights were recorded. Root and shoot growth of beans and tomatoes are evaluated with and without nanoparticles. By changing the exposure time to nanoparticles, its influence is investigated as well. It is observed that depends on concentration, exposure time and plant species, GNP has negative effects on the germination and seedling growth.
Keywords: graphene; germination; tomatoes; beans; LITHIUM-ION BATTERIES; NANOPARTICLES; Agriculture; Computer Science